2021
DOI: 10.1007/s40258-021-00687-9
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccine Demand and Financial Incentives

Abstract: Background Public health experts estimate that only very high COVID-19 vaccine uptake levels can result in herd immunity. Objective This study’s main objective was to evaluate the impact of vaccine price levels, including payments, and the efficacy levels on COVID-19 vaccine demand. Methods Data for this study were collected from an online survey of 2000 US individuals aged 18 years and older, which included a set of contingent valuation ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 34 publications
3
17
1
Order By: Relevance
“…The maximum lottery reward was listed at $1 million because that is the highest amount that has been proposed for such policies (or implemented). The maximum amount of the cash policy was $1000 because debates about financial incentives for COVID-19 have focused on this amount more than any other [6] , [33] , [34] , [35] and, while larger amounts may be effective, they are also considered excessive unlikely to be implemented [33] , [34] , [35] . The specific mandates tested were selected because they were currently debated and soon to be implemented in parts of the US.…”
Section: Methodsmentioning
confidence: 99%
“…The maximum lottery reward was listed at $1 million because that is the highest amount that has been proposed for such policies (or implemented). The maximum amount of the cash policy was $1000 because debates about financial incentives for COVID-19 have focused on this amount more than any other [6] , [33] , [34] , [35] and, while larger amounts may be effective, they are also considered excessive unlikely to be implemented [33] , [34] , [35] . The specific mandates tested were selected because they were currently debated and soon to be implemented in parts of the US.…”
Section: Methodsmentioning
confidence: 99%
“…Monetary incentives, particularly for the already-vaccinated to get a booster – also affected willingness. Although early research on monetary incentives for COVID-19 vaccination showed that incentives had little effect on vaccine preferences ( Kreps et al, 2021 ) and research on previous vaccines showed that individuals were willing to pay for the vaccine ( Carpio et al, 2021 ), growing research has shown that incentives can help overcome reluctance get the COVID-19 vaccine ( Campos-Mercade et al, 2021 ). The same appears to be true regarding boosters.…”
Section: Discussionmentioning
confidence: 99%
“…Additional studies, employing a range of methodologies, have examined the influence of vaccine attributes themselves on public acceptance. These attributes include efficacy ( Kaplan and Milstein, 2021 ; Kreps et al, 2020 ; Motta, 2021 ; Schwarzinger et al, 2021 ), technology ( Dror et al, 2021 ; Motta, 2021 ), cost/financial incentives ( Campos-Mercade et al, 2021 ; Carpio et al, 2021 ; Kreps et al, 2021 ), and manufacturer ( Kreps et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…By 4 April 2022, 11.25 billion doses of vaccine had been administered worldwide ( World Health Organization, 2022a ). Public health experts estimate that only a very high level of SARS-CoV-2 vaccination can induce mass immunity ( Carpio et al, 2021a ; Carpio et al, 2021b ). However, as the virus rages, the economies of many low-income countries have been seriously affected.…”
Section: Introductionmentioning
confidence: 99%